The blackbird girls - Blankman, Anne (Puffine Books, 2021)
Sworn enemies and fifth-grade classmates, Valentina Kaplan and Oksana Savchenko are sent from their home in Pripyat, Ukraine, to live with Valentina's grandmother in Leningrad after the 1986 Chernobyl nuclear power plant explosion. Oksana, whose abusive father perished in the accident and whose mother is hospitalized, resents being sent with Valentina, because she's been taught her whole life to hate Jews. Yet, after seeing the warm relationship between Valentina and her grandmother Rita, Oksana begins to question the lies she's been told about herself and others, and begins a friendship with Valentina.